Engraftment and outcome after autologous stem cell transplantation in plerixafor‐mobilized non‐Hodgkin's lymphoma patients. Issue 5 (30th September 2013) - Varmavuo, Ville; Rimpiläinen, Johanna; Kuitunen, Hanne; Nihtinen, Anne; Vasala, Kaija; Mikkola, Maija; Kutila, Anu; Lehtonen, Päivi; Kuittinen, Taru; Mäntymaa, Pentti; Nousiainen, Tapio; Kuittinen, Outi; et al.
<x xml:space="preserve">Abstract</x> Background Plerixafor is used in combination with granulocyte–colony‐stimulating factor to enhance the mobilization of hematopoietic stem cells. Limited data are available in regard to effects of plerixafor on posttransplant outcomes in chemomobilized patients who appear to mobilize poorly. Study Design and Methods Eighty‐nine chemomobilized patients with non‐Hodgkin's lymphoma (NHL) were included in this retrospective study. Thirty‐three patients had received plerixafor preemptively (plerixafor group) and 56 patients served as controls. Posttransplantation outcomes including infections, hematologic recovery, and relapse were recorded. Results The median fold increase of CD34+ cells after the first plerixafor dose was 4.1 in patients mobilized with chemotherapy plus filgrastim and 7.2 in those mobilized with chemotherapy plus pegfilgrastim (p = 0.027). The median number of collected CD34+ cells was 3.5 × 106 CD34+ cells/kg in the plerixafor group and 4.2 × 106 CD34+ cells/kg in the control group (p = 0.076). Early engraftment was comparable between the groups (10 days for neutrophils >0.5 × 109/L and 14 days for platelets >20 × 109/L, respectively). Also late engraftment within 12 months was comparable except higher hemoglobin level at 3 months in the control group (121 g/L vs. 112 g/L, p = 0.009). Progression‐free survival at 1 year after autologous stem cell transplantation (ASCT) was 79% in the plerixafor group and 86% in the control group (p = 0.399). Conclusions Long‐term engraftment and outcome after ASCT seem to be comparable in NHL patients receiving plerixafor compared to chemomobilized patients. These observations support the use of plerixafor in patients who mobilize poorly.